Cardiac tissue engineering: current state-of-the-art materials, cells and tissue formation - Rodrigues,Isabella Caroline Pereira (2018)
ABSTRACT Cardiovascular diseases are the major cause of death worldwide. The heart has limited capacity of regeneration, therefore, transplantation is the only solution in some cases despite presenting many disadvantages. Tissue engineering has been considered the ideal strategy for regenerative medicine in cardiology. It is an interdisciplinary field combining many techniques that aim to maintain, regenerate or replace a tissue or organ. The main approach of cardiac tissue engineering is to create cardiac grafts, either whole heart substitutes or tissues that can be efficiently implanted in the organism, regenerating the tissue and giving rise to a fully functional heart, without causing side effects, such as immunogenicity. In this review, we systematically present and compare the techniques that have drawn the most attention in this field and that generally have focused on four important issues: the scaffold material selection, the scaffold material production, cellular selection and in vitro cell culture. Many studies used several techniques that are herein presented, including biopolymers, decellularization and bioreactors, and made significant advances, either seeking a graft or an entire bioartificial heart. However, much work remains to better understand and improve existing techniques, to develop robust, efficient and efficacious methods.